A Review of Research on Multimodal Metaphors in Different Genres - Qingwen, Bai (International Journal of Humanities and Education Development (IJHED), 2025)
This paper reviews the research on the application of multimodal metaphors in major genres such as advertisements, comics and movies, as well as emerging genres such as documentaries, posters and operas. It is found that the importance of multimodal metaphor research has become more and more prominent in the academic field, and the expansion of the scope of genres studied has not only enriched the application of metaphor theory, but also provided new perspectives and tools for cultural communication and international image building. Finally, this paper discusses the problems existing in the current research on multimodal metaphors in different topics, for example, the current research often faces the problem of small sample capacity, which limits the wide applicability and depth of the research results, and many of the studies still remain in the stage of superficial application analysis of theories, failing to dig deeper into the deeper mechanism and complexity of the interaction between multimodal metaphors and audiences, and puts forward suggestions for the future research.